2007
DOI: 10.1002/elps.200600583
|View full text |Cite
|
Sign up to set email alerts
|

Tris interference in IEF and 2‐DE

Abstract: When dried IPGs are hydrated with protein solutions, the concentration of protein and other ionic constituents is constant throughout the strip. Tris, initially present at a very low concentration, focuses during IEF and accumulates in the gradient at a pH corresponding to its pK(a) at the operative temperature of electrophoresis. Tris focuses more rapidly than many basic proteins, and concentrates into a localized zone of increased conductivity which coincides with a precipitous voltage drop in that vicinity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…100 μ g of total protein per sample was used to hydrate immobilized pH gradients, pH 3 to 10 for 6 hours. Isoelectric focusing and 2-dimensional electrophoresis were performed as previously described 9. 2D gels were stained for total proteins with SYPRO Ruby (Invitrogen) or Coomassie Brilliant Blue (CCB; Proteome Systems) according to the manufacturers instructions.…”
Section: Methodsmentioning
confidence: 99%
“…100 μ g of total protein per sample was used to hydrate immobilized pH gradients, pH 3 to 10 for 6 hours. Isoelectric focusing and 2-dimensional electrophoresis were performed as previously described 9. 2D gels were stained for total proteins with SYPRO Ruby (Invitrogen) or Coomassie Brilliant Blue (CCB; Proteome Systems) according to the manufacturers instructions.…”
Section: Methodsmentioning
confidence: 99%
“…vertical lanes without protein content in the 2‐D map, which are evident as gaps in zones near the cathode. Specific factors are already known to contribute to the generation of basic zones devoid of proteins, such as large amounts of low molecular weight components like salt or buffer present in an IPG‐strip 7, but there may be other contributing factors as well. Indeed, other known effects such as hydrolysis of amide groups present in polyacrylamide 8 and the electro‐osmosis caused by hydroxide‐ions 9 may also contribute to these basic gaps.…”
mentioning
confidence: 99%
“…There is only limited published material on this subject although Smejkal et al. reported that phosphate could cause gel collapse, but did not comment if this could be caused by other ions.…”
Section: Discussionmentioning
confidence: 99%
“…Any current flow in an aqueous medium requires ion movement and water will accompany that ion flow. If the water flow is excessive then the gel can collapse near the electrodes and the electric field is likely to be disturbed . Furthermore, excessive water flow will lead to over swelling of central parts of the IPG strip resulting in poor resolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation